The historiography of Late Republican Civil War - Lange, Carsten Hjort,; Vervaet, Frederik, (Historiography of Rome and Its Empire;, 2019)
The Historiography of Late Republican Civil War is part of a burgeoning new trend that focuses on the great impact of stasis and civil war on Roman society. This volume specifically concentrates on the Late Republic, a transformative period marked by social and political violence, stasis, factional strife, and civil war. Its constitutive chapters closely study developments and discussions concerning the concept of civil war in the late republican and early imperial historiography of the late Republic, from L. Cornelius Sulla Felix to the Severan dynasty.